2017
DOI: 10.1038/s41598-017-13918-8
|View full text |Cite
|
Sign up to set email alerts
|

Punishing second-order free riders before first-order free riders: The effect of pool punishment priority on cooperation

Abstract: Second-order free riders, who do not owe punishment cost to first-order free riders in public goods games, lead to low cooperation. Previous studies suggest that for stable cooperation, it is critical to have a pool punishment system with second-order punishment, which gathers resources from group members and punishes second-order free riders as well as first-order free riders. In this study, we focus on the priority of punishment. We hypothesize that the pool punishment system that prioritizes second-order pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For instance, it was found that pool punishment can stabilize cooperation if second-order free riders are also punished [21,22]. In addition, the secondorder free-riding problem was analyzed in [23][24][25].…”
Section: Sanctioning Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was found that pool punishment can stabilize cooperation if second-order free riders are also punished [21,22]. In addition, the secondorder free-riding problem was analyzed in [23][24][25].…”
Section: Sanctioning Systemmentioning
confidence: 99%
“…For simplicity, we will drop the arguments in g( f , z, d) and write simply g. To characterize the equilibrium point at the interior of the simplex, we consider the Jacobian of System (24), which has the following form:…”
Section: Effect Of D In the Interior Equilibrium Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…In larger-scale societies, it can be effective to establish systems other than peer reward and punishment. The pool punishment system and/or the leader support system are important candidates for solving the problem [27][28][29][30][31][32] . The limitations of peer reward and punishment emphasize the importance of investigation into how these systems emerge and are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies explored the conditions under which cooperation is evolutionarily stable. However, a number of theoretical and experimental studies have found that free riders can also gain if there are perfect cooperators who cooperate unconditionally, allowing free riders to invade cooperative regimes [13][14][15][16][17][18] . For this reason, researchers call perfect cooperators second-order free riders and are interested in eliminating them.…”
mentioning
confidence: 99%